Use of Surface Modified Calcium Oxide Nanoparticle in Immobilizing of Lead and Cadmium Contaminated Soil - Okponmwense Moses; Osaretin Festus Agbonsalo (Department of Chemistry Faculty of Science and Technology Walisongo, 2022)
Remediation is vital in advancing the agriculture yield and decreasing the hazard of food poisoning in contaminated soil. The aim of this study was to remediate lead and cadmium contaminated soil from Evbareke spare parts market using surface modified calcium oxide nanoparticle (SMCON). Soil samples were collected from Evbareke spare parts market, Benin City, Edo state Nigeria, using quadrant sampling method at the depth of 0-15cm using soil auger. The soil samples obtained were physicochemically and geochemically characterized. The SMCON was synthesized and characterized using Fourier Transform-Infra Red, Scanning electron spectroscopy and x-ray diffraction. A leaching experiment was carried out to authenticate the immobilization efficiency and capacity of SMCON on the lead and cadmium in the contaminated soil. The SMCON efficiency for lead and cadmium immobilization in the contaminated soil increased with increase in immobilizer up to the optimum 4% of SMCON in contaminated soil for lead and ≤1% of SMCON for cadmium. Likewise, the immobilization capacity of SMCON in the contaminated soil also revealed that more of lead and cadmium were immobilized as SMCON content in the contaminated soil mixture increased, thereby disallowing leaching of lead and cadmium from the contaminated soil. The SMCON effectively decreased the lead and cadmium in the soil by in situ adsorption, ion exchange and complexation mechanism thus reducing its accessibility for uptake by plants and its transmission to man and animals.